Specifically unmethylated cytidylic-guanylate sites in Herpesvirus saimiri DNA in tumor cells. - Desrosiers, R C (1982)
The restriction endonucleases MspI (CCGG), HpaII (CCGG), FnuDII (CGCG), and HaeIII (GGCC) were used to study the methylation of Herpesvirus saimiri DNA in tumor cells taken directly from tumor-bearing animals. No evidence was found for methylation of the 5' terminal C in the sequence CCGG or of the internal C in the sequence GGCC, but extensive methylation of CG was detected. Fifteen HpaII sites and 17 FnuDII sites were detected in the unique DNA region of the H. saimiri strain used. Twenty-eight of the 32 sites were methylated in greater than 90% of the viral DNA molecules in tumor cells, but the remaining 4 sites were unmethylated in greater than 95% of the viral DNA molecules in tumor cells. The locations of the four specifically unmethylated sites were mapped and appeared to be identical in the four different induced leukemias examined (one owl monkey and three white-lipped marmosets). The nonproducer 1670 tumor cell line, in continuous passage for over 7 years, contained four similar specifically unmethylated sites. Possibilities for the physiological significance of the unmethylated sites are discussed.